Physiological response in table tennis players of professional group and amateur group during a seven-game match - Yu, T.; Wang, Y. F.; Tang, C.; Chen, C.; Yu, J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Biochemical data collected before and after training have been instrumental in designing a training and physical fitness program for table tennis athletes, enabling precise control over training intensity and exhaustion levels at each stage (1). Despite existing research on the energy metabolism during multi-ball feeding training in table tennis, theres limited understanding of energy utilization during actual matches. This study, therefore, seeks to investigate the physiological responses by table tennis players during a match. METHODS: This study involved 26 table tennis players, split evenly between 13 professional and 13 amateur athletes. Each participant played 7 games in a match, with evaluations conducted before, during, and after the match on variables such as blood lactate acid, body temperature, blood glucose, heart rate, perceived exertion, and biceps brachii muscle circumference. RESULTS: The study revealed that professional athletes exhibited significantly higher blood lactate acid levels than amateur athletes following the seventh game (5.3±2.1 mmol/L vs. 4.1±1.9 mmol/L), and at the third (6.5±2.7 mmol/L vs. 5.1±1.5 mmol/L), seventh (5.6±2.7 mmol/L vs. 4.8±1.7 mmol/L), and tenth minutes (4.8±1.5 mmol/L vs. 4.1±2.9 mmol/L) post-match. Conversely, amateur athletes showed significantly higher heart rates at baseline (68±2.7 bpm vs. 61.5±3.6 bpm) and ten minutes after the match (73.2±2.1 bpm vs. 66.4±3.7 bpm) compared to professionals. Additionally, amateur athletes perceived exertion ratings were significantly higher than professionals at the fifth (12.6±1.8 vs. 9.3±2.4) and tenth minutes (10.7±1.9 vs. 7.5±2.2) post-match. However, no significant differences were observed in blood glucose, body temperature, and muscle circumference between the groups. CONCLUSION: This studys results demonstrate that professional athletes exhibit higher blood lactate acid levels during the recovery period than amateur athletes, indicating more intense competition and engagement levels among professionals. Despite facing higher competition intensity, professional athletes report significantly lower perceived exertion ratings, likely reflecting their accustomedness to rigorous training regimes. Additionally, professionals show quicker heart rate recovery post-match, suggesting superior readiness for subsequent high-intensity encounters. These findings highlight a link between anaerobic metabolism efficiency and athletic skill level, suggesting that enhancing physical capabilities can significantly boost competitiveness in players with advanced skills.